1996
DOI: 10.1038/sj.bdj.4809033
|View full text |Cite
|
Sign up to set email alerts
|

Electronic infrared thermography as a dental research technique

Abstract: Electronic infrared thermography is an imaging modality for the accurate quantification of surface temperature. It has been used in medicine since the 1960s but its use in dentistry has been limited. Its use in dentistry could, however, be very useful, for example in objectively quantifying post-surgical inflammation and studying the effects of treatment with agents such as analgesics and anti-inflammatory drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
3
11
1
Order By: Relevance
“…This was previously demonstrated in a pilot study reporting a temperature increase 3 days and 5 days post-operatively compared with the baseline temperature. 4 However, the present study showed decreased temperature of the control side and no change of the operated side compared with the pre-operative examination. The background of this apparent discrepancy is unknown, but may be related to variations in skin temperature over time.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…This was previously demonstrated in a pilot study reporting a temperature increase 3 days and 5 days post-operatively compared with the baseline temperature. 4 However, the present study showed decreased temperature of the control side and no change of the operated side compared with the pre-operative examination. The background of this apparent discrepancy is unknown, but may be related to variations in skin temperature over time.…”
Section: Discussioncontrasting
confidence: 39%
“…It is easy to use, non-invasive and relatively inexpensive to acquire and maintain. As inflamed tissue is characterised by liberation of heat, thermography has been used to detect inflammation after the surgical removal of mandibular third molars 4,19 and to detect nerve injuries. 10,13,14 Moreover, a higher skin temperature on the affected side has been shown in a patient with Frey's syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 20-min equilibration period is recommended before thermographic imaging of skin should be performed (Biagioni et al . 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above studies it can be concluded that, IRT can be successfully used for temperature monitoring of the dental tissue and optimization of sterilization process. Other applications of infrared thermography in dental sciences include evaluation of craniomandibular disorders [157], detection of carotid occlusal disease [158], quantification of the effects of post-surgical inflammation [159,160].…”
Section: Dental Diagnosismentioning
confidence: 99%